Sticky costs: An Empirical Study in Brazilian and the North American Companies of the Energy Sector - Michele Bueno dos Santos, Michele; Catapan, Anderson; Gonçalves de Oliveira, Antonio; Soares, Isabel (REBRAE, 2017)
This study aims to determine the presence of stick costs (sticky costs) in Brazilian and US power companies. To this end, we collected data revenues, sold merchandise cost and taxes of 33 Brazilian power companies that are listed on the BM & FBOVESPA and 25 American companies of the same sector that trade their shares on the NASDAQ and the NYSE during the years 2004 to 2013. The research findings showed that the sticky costs can be verified in the Brazilian context, since for every percentage increase of 1% of revenue the variable costs increased 1.32%, while for 1% decrease in revenues, expenses 0.78% decrease variables. Since, in the American context, there has been the presence of sticky costs, given the linearity of the increase and decrease of the variable costs due to increased or decreased revenue. These results show the differences in the management of Brazilian and North American power companies.